The ammonia absorption spectrum between 4700 and 5650 cm−1. (December 2022) - Cacciani, P.; Čermák, P.; Vander Auwera, J.; Campargue, A.
Highlights: 9110 absorption lines were measured in four room temperature spectra of ammonia recorded by Fourier transform spectroscopy. Theoretical spectra available in the literature and lower state combination difference relations were used to assign the 14 NH3 lines. 6562 transitions were assigned to 61 vibrational bands of 14 NH3 providing 2216 upper state energy levels, most of them being newly determined. The assigned transitions represent over 99.5% of the room temperature 14 NH3 integrated absorption measured in the region. Deviations of measured intensities from theoretical predictions are interpreted as due to intensity transfers between resonant lines. Abstract: Room temperature absorption spectra of ammonia were recorded by high-resolution Fourier transform spectroscopy in the 4700–5600 cm − 1 range at four pressures (13, 46, 140, and 304 Pa). Additionally, we use an existing Kitt Peak spectrum to extend the analysis up to 5650 cm − 1 . In total, 9110 absorption lines with intensity ranging from 1 × 10 − 25 to 1.6 × 10 − 20  cm/molecule were retrieved, for the two principal isotopologues. Another Kitt Peak spectrum was used to identify 505 15 NH 3 transitions within the experimental line list. The rovibrational assignments of the 14 NH 3 lines relied on the position and intensity agreement with the C2018 theoretical line list (Coles et al. JQSRT 2018;219 199–212) and were validated by the systematic use of Lower State Combination Difference (LSCD) relations. In the process, a number of intensity transfer between nearby transitions were identified. Finally, 6562 transitions were assigned to 61 vibrational bands of the main isotopologue, 14 NH 3, representing 98.85% of the C2018 integrated absorption at room temperature in the region. The upper state empirical energy of a total of 2215 rovibrational levels of 14 NH 3 were derived. Most of them are newly reported. The comparison with the current HITRAN2020 list is discussed. A recommended line list for ammonia in natural isotopic abundance is provided for the studied region.